Efeito do estabelecimento de relações simbólicas de coordenação sobre a emissão de respostas de ajuda - Gomes, Renata Cristina (Universidade Federal de São Carlos, 2024)
This study aimed to investigate how the presentation of a request for help influences the likelihood of people being willing to help. The study was conducted with two groups of participants, one experimental and one control, who were asked to report their recent problems and then were presented with a request for help. The experimental group was presented with additional statements that established a relationship of coordination between the current problem and the participants' own problems that they had just reported. The control group was only presented with a simple request for help. The results showed that the experimental group was more likely to respond to the request for help, with seven out of eight participants contacting the second experimenter and five of them actively participating in the research. In contrast, in the control group, only half of the participants made contact and three of them agreed to participate. The authors hypothesized that by comparing both situations when requesting help, the experimenter facilitated the establishment of symbolic relations of coordination between such situations, which apparently increased the probability that the request for help would evoke responses. The results suggest that the use of this strategy - comparing the experiences lived by the client with those experienced by others - can be expanded in psychotherapy and other contexts aimed at developing empathy and sensitivity towards others. However, the results need to be considered with caution due to methodological limitations.
The effect of establishing symbolic coordination relations on the emission of helping responses
Keywords: Respostas de ajuda; Relações simbólicas; Coordenação; Helping behavior; Symbolic relations; Coordination; CIENCIAS HUMANAS::PSICOLOGIA